The legal status of religious minorities: Exploring the impact of the European Court of Human Rights - Fokas, Effie (Social compass, 2018)
In the last 25 years the European Court of Human Rights (ECtHR) has evolved into a venue where some of the most contentious questions related to religion in European society are addressed. This article focuses on the grassroots level impact of the ECtHR in the domain of legal status of religious minorities. In light of scholarly debates questioning the direct effects of courts on the issues they address (i.e., legal reform and policy change), the research on which this article is based explores the nature and extent of the Court's indirect effects on the legal status of religious minorities: how and to what extent does the ECtHR impact upon religious minorities in terms of their conceptions of, discourse around, and mobilisations pursuing their legal status-related rights? This question is addressed through results of empirical qualitative research conducted at the grassroots level in four country cases - Greece, Italy, Romania and Turkey.